A systematic review of gender‐specific rates of unipolar and bipolar disorders in community studies of pre‐pubertal children. (5th December 2013) - Douglas, Jessica; Scott, Jan
<x xml:space="preserve">Abstract</x> Objectives Gender‐specific rates of unipolar and bipolar disorders are well established for cases with post‐pubertal onset. However, there is less certainty about these rates in pre‐pubertal children. We undertook a systematic review of community studies that report gender‐specific rates for unipolar and bipolar disorders in young children, particularly cases of major depression and mania. Method Computer databases (Medline, EMBASE, Index to Theses, and PsychInfo) were searched for non‐clinical observational studies using recognized diagnostic criteria to identify unipolar and bipolar disorders in children aged ≤12 years. A meta‐analysis was undertaken to calculate pooled odds ratios (ORs) for caseness for major depression by gender. The limited data on bipolar disorder were summarized. Results Analysis of 12 studies (>15, 000 children), indicated that the community prevalence of unipolar disorders was higher in boys (1.3%) than in girls (0.8%). Rates of major depression were low (0.61%), but boys were significantly more likely to meet diagnostic criteria than girls (OR = 1.61; 95% confidence interval: 1.11–2.35). Five studies, assessing >5, 000 children, identified only one case with a probable diagnosis of mania. Conclusions This systematic review suggests that boys aged ≤12 years are significantly more likely to experience major depression than girls. However, in younger children, community rates of major depression are low, and it is frequently suggested (but not proven) that most cases are comorbid. The absence of mania suggests either that childhood bipolar phenotypes do not resemble post‐pubertal onset cases or that there are problems of case ascertainment.